Bronchoscopic bullectomy with a one‐way endobronchial valve to treat a giant bulla in an emphysematic lung: a case report. (27th January 2015) - Hou, Gang; Wang, Wei; Wang, Qiu‐yue; Kang, Jian
Abstract: The conventional treatment for giant bullae in patients with chronic obstructive pulmonary disease is surgical bullectomy, but it is not possible in some patients with poor lung function. Bronchoscopic bullectomy involving implantation of an endobronchial valve (EBV) has emerged as a potential alternative. Here we describe how EBV implantation in a bullous emphysema with a giant bulla in the right middle lobe led to elimination of the bulla and improvements in pulmonary function, 6‐min walking distance during the 1‐year follow‐up. Our case suggests that bronchoscopic bullectomy with an EBV can be a safe and effective alternative to surgical bullectomy.